On the fatigue behavior of differently deep rolled conditions of SAE 1045 in the very-high-cycle fatigue regime. (October 2021) - Saalfeld, Stephanie; Krochmal, Marcel; Wegener, Thomas; Scholtes, Berthold; Niendorf, Thomas
Highlights: Major failure mode in deep rolled specimen in the VHCF regime is related to non-metallic inclusions. A more pronounced residual stress stability is found for specimen deep rolled at 250 °C. Increase in fatigue strength (> 10 7 cycles) was revealed for room temperature deep rolled specimen. Fatigue life contribution of crack initiation and short crack growth play a subordinate role. Changes in the fatigue behavior are rationalized based on the equilibrium state of residual stresses. Abstract: Very-high-cycle fatigue (VCHF) tests were performed on differently deep rolled conditions of SAE 1045 steel. The dominant failure mode in the VHCF regime is linked to internal material defects leading to the well-known fish-eye fracture appearance. Despite lower residual stress stability, superior fatigue strength was observed for room-temperature deep rolled conditions as compared to counterparts deep rolled at elevated temperature. Crack initiation and advance is promoted by relatively higher and more stable tensile residual stresses in the core of the high-temperature deep rolled specimen, i.e., within sample volumes where cracks are initiated, eventually resulting in the inferior fatigue strength seen.